Demographic and academic factors affecting research productivity at the University of KwaZulu- Natal - North, D; Zewotir, T; Murray, M (South African Journal of Higher Education, 2011)
Research output affects both the strength and funding of universities. Accordingly university academic staff members are under pressure to be active and productive in research. Though all academics have research interest, all are not producing research output which is accredited by the Department of Education (DOE). We analyzed the demographic and academic factors that affect DOE recognized research productivity of academics at the University of KwaZulu-Natal (UKZN) between 2004 and 2008. The results show that the demographic and academic profiles of staff that produce research output differ from faculty to faculty. Thus, the intervention strategies that increase the number of research productive academics should be faculty based rather than being university based.